2017
DOI: 10.1007/s00198-017-3912-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep apnea and low bone mass in adults: a systematic review and meta-analysis

Abstract: An association between sleep apnea and low bone mass in adults is plausible, but supporting evidence has a risk of bias and is inconsistent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…When appraising the association between the severity of OSA (represented by the AHI) and bone density (represented by bone density [g/cm 2 ] or T-score) in adults, inconsistent findings have been reported. On the one hand, the severity of OSA was negatively associated with bone density (Eimar et al 2017), whereas on the other hand, a positive association between the severity of OSA and bone density was reported (Sforza et al 2013). Also, other investigators have reported no significant associations between the severity of OSA and bone density (Mariani et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When appraising the association between the severity of OSA (represented by the AHI) and bone density (represented by bone density [g/cm 2 ] or T-score) in adults, inconsistent findings have been reported. On the one hand, the severity of OSA was negatively associated with bone density (Eimar et al 2017), whereas on the other hand, a positive association between the severity of OSA and bone density was reported (Sforza et al 2013). Also, other investigators have reported no significant associations between the severity of OSA and bone density (Mariani et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Apneic episodes cause hypoxia, which in turn leads to metabolic changes that are harmful to bones [5]. A number of researchers have reported an association between sleep apnea and low bone mass, but the supporting evidence is subject to debate [10, 11]. Osteoporosis and vertebral fractures, on the other hand, have been linked to increased prevalence of OSA as a secondary consequence [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing evidence has suggested that sleep characteristics, including sleep apnea and nighttime and daytime sleep duration, are related to osteoporosis. Some studies have demonstrated an association between more severe sleep apnea and increased risk of osteoporosis 3 , 4 . Others have examined the relationship between nighttime sleep duration and bone health.…”
Section: Introductionmentioning
confidence: 99%